Spatial Analysis of the Occurrence of Multi-Drug Resistance (MDR) Escherichia coli in Pet Dogs in Kupang City - Kallau, Novalino H.G.; Sanam, Maxs U.E.; Utami, Tri; Sitompul, Yeremia Y. (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Antibiotic resistance is an important health problem and a threat to public health. Dogs as pets can be both spreaders and reservoirs of antibiotic-resistant bacteria. Based on spatial analysis, this study aims to determine the distribution pattern of multi-drug resistance (MDR) Escherichia coli found in pet dogs in Kupang City. The spatial analysis method is based on the convex hull technique, elementary analysis of disease, and the Nearest Neighbour Index (NNI). Information on antibiotic-resistant E. coli has been obtained from the laboratory analysis results, and secondary data was obtained for spatial analysis. The results of this study have shown that the distribution pattern of the incidence of MDR E. coli in the City of Kupang in 2020 is a clustered pattern with the Nearest Neighbor Index (NNI) value of 0.783, which is higher than the NNI AMR E. coli in the City of Kupang of 0.763. The incidence of MDR E. coli that has occurred in domesticated dogs takes place with a prevalence rate of 35% in an area of 5079 Ha. These results have shown that the incidence of MDR E. coli has spread to several areas in Kupang City and is a threat to public health. It requires appropriate prevention and control measures by implementing good hygiene and sanitation in the relationship between humans and their pets.